The Influence of the Buddy Reading Method Assisted with Flipbook Media on Reading Comprehension of Class V Students - Nurfiana Nurfiana; Sulfasyah Sulfasyah; Tarman Tarman (Universitas Muhammadiyah Enrekang, 2024)
Research on the Buddy Reading Method Assisted by Flipbook Media on the Interest and Reading Comprehension Ability of Class V Students at SD Gugus III Paraikatte District. Bajeng Kab, Gowa, Masters Program, Muhammadiyah University of Makassar Supervised by Sulfasyah and Tarman. This research aims to determine the effect of Buddy Reading helping with flipbook media on the interest and reading comprehension abilities of fifth grade students. This research uses a quasi-experimental design involving an experimental class and a control class. The research population was all fifth graders who were members of an elementary school group in the same zone in Gowa Regency, South Sulawesi Province. The research sample was two fifth grade students selected randomly from the group mentioned above. The instruments used to collect data were questionnaires and reading comprehension tests. Descriptive data analysis shows that there is an increase in students' interest and reading comprehension abilities after teaching reading comprehension using the Buddy Reading Method. The results of inferential statistical analysis using Manova showed that there were differences between the control and treatment classes regarding reading interest and reading comprehension ability, with mark scores. 0.000 < 0.05. Thus, the buddy reading method influences the reading interest and reading comprehension abilities of fifth grade students in this study.